Characterisation of Non-Associative Ordered Semigroups by the Properties of F-Ideals - Kausar, Nasreen; Munir, M.; Kousar, Sajida; Gulistan, M.; Anitha, K. (TAYLOR & FRANCIS LTD, 2020)
In this article, we present brief description on R-OAG-gpd (regular ordered AG-groupoid) and IR-OAG-gpd (intra-regular ordered AG-groupoid) by using FL-ideal, FR-ideal, FQ-ideal, FB-ideal, FB-ideal, FGB-ideal.
Keywords: FL-ideal; FR-ideal; FI-ideal; FQ-ideal; FB-ideal; FGB-ideal; Mathematics